Полкові емблеми доби гетьманщини: історичне походження та особливості символіки - Пічієнко, М. Г. (ХНУРЕ, 2019)
Ukraine is a young state, that has a lot of unexplored questions in historical and language-related sciences, among which is heraldry. This area is in the process of establishment, so that any studies should contribute to the development and formation of this interesting science. In this work we will consider the history of regimantal system-setting, describe the Cossack regimental emblems, reveal their characteristic features and investigate their influence on modem heraldry